ANALISIS PENGELOLAAN KEUANGAN RETRIBUSI PARKIR PEGAWAI NEGERI SIPIL DI LINGKUP PEMERINTAHAN KOTA PALU - Dewi, Fitri Rosmala (Katalogis, 2016)
This research aims to determine and analiyze: 1) financial management of civil servants’ parking levies in Palu, which includes planning, implementation, reporting, and auditing; 2) the effectiveness of financial management of civil servants’ parking levies in Palu. Type of this research is descriptive and population consist of goverment officials in The Agency of Revenue, Administration, and Local assets and The Office of Transportation, Palu. The results show that the management of parking subscription of civil servants in Palu has been effective; yet, the management of parking facilities remains poor. The reception of parking fees is effective as it shows an increase from Rp. 1.755.500.000,- in 2014 to the amount of Rp. 2.037.880.000,- in 2015.